Analisis Produktivitas Pipa Kotak Galvanis dengan Metode Objective Matrix dan Root Cause Analysis - Sabrina, Vina; Aryanny, Enny (Ekonomis: Journal of Economics and Business, 2025)
This study aims to evaluate and determine the level of partial productivity in the iron pipe production unit at CV. XYZ. The methods used in this study include Objective Matrix (OMAX), and Root Cause Analysis (RCA) with Five Whys Analysis and 5W + 1H (What, Where, When, Why and How) tools. The results of the study obtained an average value of partial productivity for raw materials of 93.54%, labor of 3,679 (stems/person/month), machine working hours of 225 (stems/hour/month), worker working hours of 222 (stems/hour/month), electrical energy of 69.58%, and defective products of 1.02%. Improvements to increase productivity levels are ensuring stakeholders carry out work based on SOPs, coordinating the arrival of raw ribbon materials according to the schedule and priority of completing raw material slithers between parties, creating intensive and regular training schedules for operators or employees, the production team needs to group production requests in a planned and organized manner so that it is necessary to add one new machine unit, creating daily to monthly electricity usage control cards, and providing incentives for workers who produce more than the target.